The effect of start block configuration and swimmer kinematics on starting performance in elite swimmers using the Omega OSB11 block - Slawson, S. E.; Conway, P. P.; Cossor, J.; Chakravorti, N.; Le-Sage, T.; West, A. A. (Procedia Engineering, 2011)
Work detailed within this paper has begun to explore the effect of altering start block set-up and swimmer stance on subsequent starting performance using the Omega OSB11 starting block. Thirty-two elite British Swimmers were tested in 12 difference configurations during which, force, timing and distance information were captured. ANOVA tests have been carried out on the overall data set, revealing significant differences in output/performance variables as a result of changing the width of the swimmers stance. In addition, a single case-study is presented demonstrating the effect stance and set-up can have for an individual athlete. Future work should look towards finding general trends that may help less experienced athletes to improve their starting performance. It is thought that more specific analysis of elite athletes may enable "ideal" set-ups to be advised to athletes to gain advantage in the start phase of a race.